การตรวจวัดซีลีเนียม(IV) ที่จำเพาะเจาะจงในตัวอย่างผลผลิตทางการเกษตร โดยใช้แคดเมียมซัลไฟด์นาโนโพรป SPECIFIC DETECTION OF SELENIUM(IV) IN AGRICULTURAL SAMPLE BY CdS-Cys-DAB FLUORESCENT NANOPROBES - Chongcharoen, Jaturong; Muangthai, Pornpimol (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This research aims to develop a selective CdS-Cys-DAB fluorescent nanoprobe for selective determination of selenium(IV) in sample such as onion. The nanoprobe consists of a cysteine-capped cadmium sulfide core and a coating layer containing selenium(IV)-induced fluorescent molecules, 3,3’-diaminobenzidine (DAB). The fluorescence intensity emitted from the selenium-binded nanoprobes was measured at 390 nm with an excitation wavelength at 280 nm. Vadidation of the nanoprobe was investigated. The fluorescence intensity of nanoprobes shows linearity that proportional to selenium(IV) quantity in the range of 1.00 - 5.00 ppm with a correlation coefficient of 0.9925. The detection limit (LOD) and quantification limit (LOQ) of this nanoprobes were 0.12 and 0.34 ppm respectively. The results of the interfering study of some metal ions on the nanoprobe response showed a high selectivity of the CdS-Cys-DAB nanoprobes towards Se(IV) ions. The nanoprobe was subsequently applied to determine selenium(IV) content in onion sample. It was found that the concentration of as low as 1.42 ppm of selenium(IV) was obtained. Based on the results, the synthesized nanoprobe should be successfully applied for further analysis of selenium(IV) content in other agricultural sample